Et kritisk posthumant subjekt? Braidottis og Haraways diskussioner om subjektivitet og det mere-end-menneskelige - Thorsen Vilslev, Birgitte (K&K - Kultur og Klasse, 2024)
This paper studies a discussion about posthumanism between the two influential feminist philosophers Rosi Braidotti and Donna Haraway in the journal, Theory, Culture & Society 23, no. 7-8 in 2006. In the journal Braidotti describes Haraway’s thinking as “high posthumanism”, while Haraway, interviewed in the journal, on the other hand is very critical of the term. She prefers thinking with other terms such as cyborgs, companion species or the Chthulucene. With the starting point in this historical discussion, the paper traces it into Braidotti’s recent book Posthuman Feminism (2021) and Haraway’s Staying with the Trouble: Making Kin in the Chthulucene (2016). A central concern in the discussion is the critical subject: How can the critical subject be understood and operate in a posthumanist framework? Can there be critical potentials in more-than-human positions and perspectives? How to think critical subjectivity as relational with other species and the material world? Based on these questions, the paper investigates posthuman feminism through more-than-human perspectives on the critical subject.